Antagonistic and Antibacterial Activity of Stapylocossus aureus and Isolates of Oral Bacteria from the Endogenous Fungus Apis dorsata Binghami Nest - Semuel, Mokosuli Yermia; Wurarah, Masje; Tuegeh, Reinny Silvana (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Apis Dorsata Binghami honey bee is a honey bee endemic to Indonesia, living naturally in the forests of Sulawesi. This study aimed to obtain isolates and characteristics of endogenous fungi antibiotic activity from Apis dorsata Binghami nest. The research consisted of isolation of fungi from beehives using potato dextro agar, pure culture of fungi, antagonist test and antibiotic test using disc diffusion method. Antibiotic test was performed on oral bacteria and Staphylococcus aureus. The results obtained six isolates of fungi from the nest of Apis dorsata Binghami, namely isolates FAB1, FAB2, FAB3, FAB4, FAB5 and FAB6. The results of the antagonist test showed that the isolates FAB2 and FAB3 had the best antagonist properties, while the FAB6 isolates had the weakest antagonist properties. The FAB2 isolate showed the best bacterial growth inhibition zone average for the isolates of oral bacteria and Staphylococcus aureus. The inhibition zone lasts up to 3 x 24 hours so that the activity of the bacteria is bactericidal. From the results of this study, it can be concluded that the endogenous fungus Apis dorsata Binghami is a potential source of antibacterial bioactives.